Rapid, simple, and sensitive detection of the ompB gene of spotted fever group rickettsiae by loop-mediated isothermal amplification - Pan, Lei (BioMed Central, 2012)
BACKGROUND: Spotted fever caused spotted fever group rickettsiae (SFGR) is prevalent throughout China. In this study, we describe a rapid, simple, and sensitive loop-mediated isothermal amplification (LAMP) assay targeting the ompB gene of spotted fever group rickettsiae ideal for application in China. The LAMP assay has the potential to detect spotted fever group rickettsiae early in infection and could therefore serve as an alternative to existing methods. METHODS: A set of universal primers which are specific 7 common species of spotted fever group rickettsiae in China were designed using PrimerExplorer V4 software based on conserved sequences of ompB gene. The sensitivity, specificity and reproducibility of the LAMP were evaluated. The LAMP assay for detecting SFGR was compared with conventional PCR assays for sensitivity and specificity in early phase blood samples obtained from 11 infected human subjects. RESULTS: The sensitivity of the LAMP assay was five copies per reaction (25 μL total volume), and the assay did not detect false-positive amplification across 42 strains of 27 members of the order Rickettsiales and 17 common clinical pathogens. The LAMP assay was negative to typhus group rickettsiae including R. prowazekii and R. typhi for no available conserved sequences of ompB was obtained for designing primers. To evaluate the clinical applicability of the LAMP assay, a total of 11 clinical samples, 10 samples confirmed serologically (3 cases), ecologically (1 case), by real-time polymerase chain reaction (PCR; 2 cases), ecologically and by real-time PCR (1 case), and serologically and by real-time PCR (3 cases) were analyzed by the ompB LAMP assay. Data were validated using a previously established nested PCR protocol and real-time PCR. A positive LAMP result was obtained for 8 of the 10 confirmed cases (sensitivity, 73%; specificity, 100%), while none of these samples were positive by nested PCR (sensitivity, 0%; specificity, 100%). CONCLUSIONS: The LAMP assay described here is the most reliable among the three methods tested and would be an ideal choice for development as a rapid and cost-effective means of detecting SFGR in China.